Penerapan Pemberian Jasa Hukum Di Bidang Kenotariatan Secara Cuma-Cuma Oleh Notaris Berdasar Undang-Undang Nomor 2 Tahun 2014 di Kabupaten Malang - Utami, Nuryanti Puji (Jurnal Ilmiah Administrasi Publik, 2017)
The Implementation of article 37 verse (1) UUJN it contains about the obligation of a notary gives free law service for the poor people with correct existencxe of notary’s instinct, it means notary must have faith authentically and inner strength about giving free help for the poor people. The qualification factors of giving free law service in notarialfield or the problems fact are 1) Because people in general, they don’t know about there is act thats regulates giving free law service in notarial field for the poor people, 2) Poorly supervision by MPD, MPW, and MPP, 3) No clear boundary about giving free law service for the poor people.